Karakteristik Fisika Kimia Tanah pada Sistem Agroforestri - Rossyda Priyadarshini; A. Hamzah; Maroeto Maroeto; B.W. Widjajani (xxxx-xxxx, 2020)
Priyadarshini R, Hamzah A, Maroeto M, Widjajani BW. 2020. Soil physico-chemical characteristics on agroforestry systems. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The composition, structure and type of vegetation are determined by land management patterns and their closely related with the organic matter input, which in turn will determine soil physico-chemical characteristics, in particular soil bulk density, organic-C, and N mineralization. This study aims to measure and compare the soil physico-chemical characteristics and nett N-mineralization, and also nitrogen leaching on agroforestri systems with different levels of tree diversity. The research was conducted on 2 (two) types of agroforestry systems with different compositions; namely simple agroforestry and complex agroforestry. The research was conducted in the Sumber Brantas sub-watershed which is located at 1150 17’00” to 118019’00” East Longitude and 7055’30” to70 57’30” South Latitude, on 3 (three) different plots for each type of agroforestry. The results showed that complex agroforestry systems had a greater input of organic matter (6.55 Mg ha-1) than simple agroforestry (4.68 Mg ha-1), with soil mineral N content of 108.2 kgha-1 and respectively. 120.2 kg ha-1 for complex agroforestry and simple agroforestry. The leached nitrate in the agroforestry systems was also greater (3.16%) than the simple agroforestry systems(1.83%) which was managed with a greater porosity in the complex agroforestry systems indicated by the lower value of soil bulk density (0.84 gcm- 3) compare with simple agroforestry (1.09 gcm-3).